2010
DOI: 10.1017/s0047279410000656
|View full text |Cite
|
Sign up to set email alerts
|

Early Occupational Aspirations and Fractured Transitions: A Study of Entry into ‘NEET’ Status in the UK

Abstract: There has been significant recent research and policy interest in issues of young people's occupational aspirations, transitions to employment and the antecedents of NEET (not in employment, education or training) status. Many have argued that changes to the youth labour market over the past 30 years have led to transitions to work becoming more individualised, complex and troublesome for many, particularly those from poorer backgrounds. However, little research has examined the connection between early uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 26 publications
8
91
0
6
Order By: Relevance
“…The extent to which emergent adulthood is a legitimate concept across all sections of society has been rigorously debated (Arnett 2007;Bynner 2005;Hendry and Kloep 2007). Some contend that young adults are more accurately experiencing "structured individualization" (Côté and Bynner 2008;Furlong and Cartmel 2007) with opportunities and pathways to adulthood still strongly influenced by young people's original location in the social structure, despite a greater sense of individual autonomy (MacDonald et al 2005;Roberts 2009;Schoon 2007;Yates et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which emergent adulthood is a legitimate concept across all sections of society has been rigorously debated (Arnett 2007;Bynner 2005;Hendry and Kloep 2007). Some contend that young adults are more accurately experiencing "structured individualization" (Côté and Bynner 2008;Furlong and Cartmel 2007) with opportunities and pathways to adulthood still strongly influenced by young people's original location in the social structure, despite a greater sense of individual autonomy (MacDonald et al 2005;Roberts 2009;Schoon 2007;Yates et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons include the expansion of full-time places in higher and further education, the raising of the school-leaving age, and the collapse of the traditional rapid entry into employment in manufacturing and heavy industry within post-industrial cities (Pollock, 1997;Yates et al, 2011). In the mid-1970s 'two-thirds of teenagers went straight into employment at age 16, at the end of the 1990s less than one in ten 16 year-olds looked for work as they completed compulsory schooling' (McDowell, 2002, p.42).…”
Section: Urban Youth Unemployment Employability and Youth Transitionsmentioning
confidence: 99%
“…Alongside this, there is a growing body of evidence on the long-term penalties for individuals when career ambitions are uncertain or unrealistic (Yates, Harris, Sabates, & Staff, 2011). It has been shown that 6 D. Hughes et al young people who were uncertain or unrealistic about their career ambitions at 16 went on to be three times more likely to spend significant periods of times being NEET, compared to their peers.…”
Section: Educationmentioning
confidence: 99%